Desenvolvimento de uma PCR multiplex para identificação de clostrídios histotóxicos - Ana Izabel Passarella Teixeira (2012)
The polymerase chain reaction (PCR) has emerged in recent years as an important technique for identification of microorganisms to be extremely sensible and versatile. This work was the developmentof a multiplex PCR for the detection and discrimination of histotoxic clostridia. The analytical sensitivity obtained was approximately 0.15 ng for C.chauvoeiand 0.015ng for other agents. No amplification occurred in the test of specificity for species Clostridium tetani(ATCC 9441), Staphylococcus aureus(ATCC 27707), Pseudomonas aeruginosa(ATCC 25319), Escherichia coli(ATCC 21986), Clostridium difficile(ATCC 9689), Proteus mirabilis(ATCC 12453) and Salmonella typhi(ATCC 9992V), confirming it. This paper presents an efficient andspecific multiplex PCR for detection and identification of clostridia histotoxics.